The Relationship Between Household Head Income and Perceptions of Nursing Service Quality Among General Patients (Journal of Social And Education Research, 2024)
This study aims to examine the relationship between the income of patients’ heads of household and their perception of nursing service quality in the inpatient rooms at RSUD Praya, Central Lombok. A quantitative cross-sectional design was employed with a sample of 67 respondents, selected using accidental sampling. Data were collected using a validated questionnaire and analyzed using univariate and bivariate methods, including the Chi-Square test. The results showed that respondents with low income were more likely to perceive nursing service quality as poor (31.3%). The Chi-Square test indicated a significant relationship between income and perceived service quality (p = 0.019 < 0.05). The study revealed that socioeconomic status, particularly income level, influences patients’ perceptions of nursing care. Respondents with lower income tended to perceive service quality as less satisfactory, potentially due to limited access or perceived staff bias, while respondents with higher income had higher expectations, leading to perceptions of lower service quality despite receiving similar care. These findings highlight the importance of considering income-related factors in healthcare management to improve patient satisfaction and equity in service delivery.